2017
DOI: 10.1371/journal.pone.0172174
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pravastatin on the normal human placenta: Lessons from ex-vivo models

Abstract: IntroductionResearch in animal models and preliminary clinical studies in humans support the use of pravastatin for the prevention of preeclampsia. However, its use during pregnancy is still controversial due to limited data about its effect on the human placenta and fetus.MethodsIn the present study, human placental cotyledons were perfused in the absence or presence of pravastatin in the maternal reservoir (PraM). In addition, placental explants were treated with pravastatin for 5, 24 and 72 h under normoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 45 publications
(67 reference statements)
0
17
0
Order By: Relevance
“…It has been shown that eNOS augments fetoplacental blood flow, placental vascularization, and fetal growth in mice (20). In addition, it has been reported that PRAV protects the endothelium by activating eNOS independent of its cholesterol-lowering actions (21). Moreover, an increase in the synthesis and activity of eNOS was found in human placental cotyledons perfused with PRAV (22).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…It has been shown that eNOS augments fetoplacental blood flow, placental vascularization, and fetal growth in mice (20). In addition, it has been reported that PRAV protects the endothelium by activating eNOS independent of its cholesterol-lowering actions (21). Moreover, an increase in the synthesis and activity of eNOS was found in human placental cotyledons perfused with PRAV (22).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, it is worth noting that recent studies have demonstrated that pravastatin has a favorable pharmacokinetic profile in pregnancy. 29 Pravastatin therapy: A case report…”
Section: Clinical Researchmentioning
confidence: 99%
“…They are commonly applied in cardiovascular diseases. 6 Moreover, more and more reports showed that statins can effectively resist myocardial infarction and improve survival rate, inhibit inflammation and apoptosis of cells, stabilize artery plaque, maintain endothelial function and eliminate free radicals. 7 – 10 Pravastatin belongs to statins.…”
Section: Introductionmentioning
confidence: 99%